Evaluation of novel Griess-reagent candidates for nitrite sensing in aqueous media identified via molecular fingerprint searching. Issue 7 (29th January 2019) - Váradi, Linda; Breedon, Michael; Chen, Fiona F.; Trinchi, Adrian; Cole, Ivan S.; Wei, Gang
Abstract : Novel Griess reagents were identified using molecular fingerprint searching and rapid experimental evaluation for the detection of nitrite in aqueous media. Abstract : The Griess reaction is the most often exploited colorimetric method for the quantitative analysis of nitrite in aqueous media. The application of the currently used reagents are associated with limitations ( e.g. linear response range). Herein, molecular fingerprint searching on well-known Griess-reagents was used as a tool for the identification of structurally similar, new reagent candidate molecules. Rapid and high-throughput experimental evaluation of the newly identified Griess-reagent candidates revealed that 14 of the 18 tested reagent candidates had equal or superior response displaying broader linear ranges and/or increased response gradient against various nitrite concentrations in aqueous media when compared to the parent compounds at room temperature.